Optimization of pentadentate bispidines as bifunctional chelators for 64Cu Positron Emission Tomography (PET) - Comba, Peter; Hunoldt, Sebastian; Morgen, Michael; Pietzsch, Jens; Stephan, Holger; Wadepohl, Hubert (Inorganic chemistry, 2013)
Pentadentate bispidine ligands (3,7-diazabicyclo[3.3.1]nonanes) are optimized for maximum complex stability and facile functionalization with respect to their coupling to biological vector molecules and/or fluorescence markers for PET (positron emission tomography) and multimodal imaging (i.e., PET and optical imaging). The pentadentate ligand with two tertiary amine donors, two p-methoxy substituted pyridines, and one unsubsituted pyridine group is shown to best fulfill important conditions for PET applications, i.e., fast complexation with CuII and high in vivo stability, and this was predicted from the solution chemistry, in particular the CuII/I redox potentials. Also, solvent partition experiments to model the lipophilicity of the CuII complexes indicate that the bis p-methoxy substituted ligand leads to cationic complexes with an appreciable lipophilicity. This is supported by the biodistribution experiments that show that the complex with the p-methoxy substituted ligand is excreted very quickly and primarily via the renal route and therefore is ideally suited for the development of PET tracers with ligands of this type coupled to biomolecules.
Im Titel ist "64" hochgestellt
Gesehen am 04.05.2021